Temperature Modulates the Secretome of the Phytopathogenic Fungus Lasiodiplodia theobromae - Félix, Carina; Duarte, Ana S.; Vitorino, Rui; Guerreiro, Ana C. L.; Domingues, Pedro; Correia, António C. M.; Alves, Artur; Esteves, Ana C. (Frontiers in Plant Science, 2016)
Environmental alterations modulate host–microorganism interactions. Little is known about how climate changes can trigger pathogenic features on symbiont or mutualistic microorganisms. Current climate models predict increased environmental temperatures. The exposing of phytopathogens to these changing conditions can have particularly relevant consequences for economically important species and for humans. The impact on pathogen/host interaction and the shift on their biogeographical range can induce different levels of virulence in new hosts, allowing massive losses in agricultural and health fields. Lasiodiplodia theobromae is a phytopathogenic fungus responsible for a number of diseases in various plants. It has also been described as an opportunist pathogen in humans, causing infections with different levels of severity. L. theobromae has a high capacity of adaptation to different environments, such as woody plants, moist argillaceous soils, or even humans, being able to grow and infect hosts in a wide range of temperatures (9–39°C). Nonetheless, the effect of an increase of temperature, as predicted in climate change models, on L. theobromae is unknown. Here we explore the effect of temperature on two strains of L. theobromae – an environmental strain, CAA019, and a clinical strain, CBS339.90. We show that both strains are cytotoxic to mammalian cells but while the environmental strain is cytotoxic mainly at 25°C, the clinical strain is cytotoxic mainly at 30 and 37°C. Extracellular gelatinolytic, xylanolytic, amylolytic, and cellulolytic activities at 25 and 37°C were characterized by zymography and the secretome of both strains grown at 25, 30, and 37°C were characterized by electrophoresis and by Orbitrap LC-MS/MS. More than 75% of the proteins were identified, mostly enzymes (glycosyl hydrolases and proteases). The strains showed different protein profiles, which were affected by growth temperature. Also, strain specific proteins were identified, such as a putative f5/8 type c domain protein – known for being involved in pathogenesis – by strain CAA019 and a putative tripeptidyl-peptidase 1 protein, by strain CBS339.90. We showed that temperature modulates the secretome of L. theobromae. This modulation may be associated with host-specificity requirements. We show that the study of abiotic factors, such as temperature, is crucial to understand host/pathogen interactions and its impact on disease.